2022
DOI: 10.1021/acs.jpcc.2c02076
|View full text |Cite
|
Sign up to set email alerts
|

Population of Subradiant States in Carbon Nanotube Microcavities in the Ultrastrong Light–Matter Coupling Regime

Abstract: Strong light–matter coupling results in eigenstates called polaritons which share the properties of both light and matter and provide a useful way to engineer electronic energies and behaviors. In this work, we study nearly monochiral (6,5) semiconducting carbon nanotubes (CNTs) in a Fabry–Pérot microcavity. Light–matter coupling leads to the formation of three bands of bright polariton states (upper, middle, and lowerresulting from coupling to the bright S11 CNT exciton and the X1 phonon sideband of the K-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The spectra exhibit derivative lineshapes with positive and negative features along the probe energy axis. These are characteristic features of Rabi contraction, where the depletion of ground-state population upon photoexcitation by the pump pulse results in a reduction in Rabi splitting, and subsequently a transient shift in peak positions 28 , 29 , 39 41 . Thus, the peak energies identified in the 2DWL spectra do not exactly match the energies of the eigenstates identified in the steady-state spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra exhibit derivative lineshapes with positive and negative features along the probe energy axis. These are characteristic features of Rabi contraction, where the depletion of ground-state population upon photoexcitation by the pump pulse results in a reduction in Rabi splitting, and subsequently a transient shift in peak positions 28 , 29 , 39 41 . Thus, the peak energies identified in the 2DWL spectra do not exactly match the energies of the eigenstates identified in the steady-state spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Figure presents the results of a single-walled carbon nanotube (SWCNT) system (∼1000 atoms) coupled to an optical cavity, which has been the subject of recent experimental interest in molecule–cavity coupling. Semiconducting SWCNTs are known to have weak photoluminescence due to low-lying optically inactive states below the so-called band-edge E 11 exciton, which is the 6th excited state, and we denote |ψ 6 ⟩ ≡ | E 11 ⟩. Figure a provides the transition dipole matrix for the pristine (6,5) SWCNT system, showing a sparse matrix with only the ground-to-E 11 (i.e., the sixth bare molecular transition) transition to be optically allowed with a large dipole moment of ∼28 au, and small dipole matrix elements between other excited states.…”
mentioning
confidence: 99%
“…Finally, we applied the pQED scheme to investigate the polaritonic properties of a single-walled carbon nanotube, a system of recent experimental interest for polaritonic applications. ,,,,,, We showed that through light–matter coupling one can red-shift the bright E 11 character of the tube below the band of dark states (which makes these materials dark to emission outside the cavity), thus enabling strong optical emission from these materials inside the cavity without the need for chemical functionalization.…”
mentioning
confidence: 99%
“…The spectra exhibit derivative lineshapes with positive and negative features along the probe energy axis. These are characteristic features of Rabi contraction, where the depletion of ground-state population upon photoexcitation by the pump pulse results in a reduction in Rabi splitting, and subsequently a transient shift in peak positions 28,29,[39][40][41] . Thus, the peak energies identified in the 2DWL spectra do not exactly match the energies of the eigenstates identified in the steady-state spectra.…”
Section: Dwl Spectroscopy Of Cnt Microcavitiesmentioning
confidence: 99%